Effect of farm and landscape variables on insect biodiversity and biotic interactions in homestead gardens - Palatty Allesh, Sinu; Krishnan, Abhiram; Baby, Ashly; Hariraveendra, M.; Viswan, Gopika; Jose, Thomas; Malaiappan, Sudharsan; Pawar, Manohar; Acharya, Pradyumna; Krishnan, Smitha (2024)
Biodiversity and biotic interactions in agro-ecosystems can be driven by local and landscape drivers, including environmental factors, management practices, and landscape characteristics. The role of natural or semi-natural area in agro-ecosystem has received considerable attention from biodiversity poor temperate regions, such as Europe and North America, where large scale commercial and intensive agricultural practices are prevalent. However, most of India situated within tropical or subtropical regions, supports greater biodiversity. India’s goal to increase agricultural production may lead to intensification through high use of agro-chemical inputs and intensive monoculture practices. Understanding how farm management and landscape variables drive biodiversity and biotic interactions that are beneficial for agriculture is a timely study for India, particularly for the regions that traditionally practiced low intensive agriculture but are now susceptible to intensification. This pilot study aims to discern the effect of landscape variables on insect biodiversity and the biotic interactions that contribute to ecosystem services such as pollination and natural biocontrol in agro-ecosystem models, such as homestead gardens. Due to the intervention of self-help groups and NGOs, a significant proportion of natural areas have been reclaimed and restored as forests. To test the hypothesis that forest cover positively affects insect diversity and insect services in croplands, we focused on winter crop fields in Mandla, Madhya Pradesh. The main research findings are that forest cover generally supports bees which are important pollinators, but croplands harbored important pest controlling agents such as parasitoid wasps and pollinators such as flies in homesteads. Built-up areas and water bodies have varied effects on different insect and pollinator groups. Certain crops are preferred for forage and nest building materials by pollinators emphasising the importance of crop plants in maintaining pollinator populations. Predation services by farmland predators are influenced by landscape composition, with forest cover and cropland area being significant drivers. These conclusions underscore the complex interactions between landscape variables, insect populations, pollinators, and natural pest control services in agricultural landscapes. While extent of forests, rangelands and crop lands play a vital role in various ecosystem services that impact crop productivity, in-depth study to understand interactive effects of the various landscape components is crucial to understand the intricacies of the interactions of these agriculturally important insects and the landscape components.